Sorafenib Reveals Anti-Arthritic Potentials in Collagen induced Experimental Arthritis Model - Gozel, Nevzat; Cakirer, Masallah; Karatas, Ahmet; Tuzcu, Mehmet; Ozdemir, Fethi Ahmet; Dagli, Adile Ferda; Koca, Suleyman Serdar (Turkish League Against Rheumatism, 2018)
Objectives: This study aims to examine the effects of sorafenib on a collagen-induced arthritis (CIA) model. Materials and methods: The study included 50 randomly selected female Wistar-albino rats (8-10-week-old, weighing between 200 g to 250 g). The rats were divided into five equal groups as control, arthritis, etanercept, sorafenib high-dose, and sorafenib low-dose groups, respectively. Arthritis was induced by injecting mixed intradermal chicken type II collagen and incomplete Freund's adjuvant. Twenty-four hours after the advent of arthritis; rats in group 3 were injected subcutaneous etanercept (6 mg/kg/week), while those in groups 4 and 5 were given sorafenib (10 or 30 mg/kg/day) orally until they were sacrificed on the 34th day. The rat claws and trunk bloods were carefully examined to note perisynovial inflammation and cartilage/bone injury through histopathology. Tissue vascular endothelial growth factor (VEGF) and VEGF receptor levels were carefully checked using western blot analysis. Results: Analysis of the experimental data showed that CIA decreased in treatments groups after 12-13 days and 34th day in contrast with the arthritis group. Histopathological examination revealed broad perisynovial inflammation and cartilage/bone breakdown in the arthritis group. Compared to the control group, tissue VEGF and VEGF receptor levels increased in the arthritis group. Sorafenib and etanercept decreased tissue VEGF and VEGF receptor levels, perisynovial inflammation, damage of cartilage/bone. Conclusion: Our findings indicate that sorafenib treatment ameliorates CIA with anti-VEGF effectiveness.
Keywords: Collagen-induced arthritis; rheumatoid arthritis; sorafenib